ANALISIS MINAT BELAJAR MATA PELAJARAN BAHASA INDONESIA SISWA KELAS III SDN - Samicha ’ Wafa; Ruri Fadhilah Kurniati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Learning interest is one of the key factors influencing the success of Indonesian language learning in elementary schools. However, some students still demonstrate suboptimal attention, engagement, and interest during the learning process, highlighting the need to examine students' learning interest and the factors influencing it. This study aimed to analyze the learning interest of third-grade students in Indonesian language subjects and identify the factors affecting their learning interest at SDN Banjarbendo. This research employed a qualitative approach with a descriptive research design. Data were collected through classroom observations, semi-structured interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis was conducted using the stages of data reduction, data display, and conclusion drawing. The findings revealed that students' learning interest was categorized as moderate, with a percentage of 69.87%, as reflected in the indicators of attention, interest, participation, and enjoyment. Among these indicators, enjoyment showed the highest achievement, whereas attention remained the aspect requiring further improvement. Students' learning interest was influenced by internal factors, including academic ability, self-confidence, study habits, and learning motivation, as well as external factors, namely teachers' roles, teaching methods and instructional media, the learning environment, and parental support. The study concludes that the teacher's role, particularly through the implementation of innovative teaching methods and instructional media, is the most dominant factor in enhancing students' learning interest. Therefore, Indonesian language instruction should be designed to be active, interactive, and contextual while strengthening collaboration between teachers and parents to create more meaningful learning experiences. ABSTRAK Minat belajar merupakan salah satu faktor yang memengaruhi keberhasilan pembelajaran Bahasa Indonesia di sekolah dasar. Namun, masih terdapat siswa yang menunjukkan perhatian, keterlibatan, dan ketertarikan yang belum optimal selama proses pembelajaran, sehingga diperlukan kajian mengenai tingkat minat belajar serta faktor-faktor yang memengaruhinya. Penelitian ini bertujuan untuk menganalisis minat belajar siswa kelas III pada mata pelajaran Bahasa Indonesia serta mengidentifikasi faktor-faktor yang memengaruhi minat belajar tersebut di SDN Banjarbendo. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data diperoleh melalui observasi, wawancara semi-terstruktur, dan dokumentasi. Keabsahan data diuji menggunakan triangulasi sumber dan triangulasi teknik, sedangkan analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa minat belajar siswa berada pada kategori sedang dengan persentase 69,87%, yang ditunjukkan melalui indikator perhatian, ketertarikan, keterlibatan, dan perasaan senang. Indikator perasaan senang memperoleh capaian tertinggi, sedangkan perhatian masih menjadi aspek yang perlu ditingkatkan. Minat belajar siswa dipengaruhi oleh faktor internal, yaitu kemampuan akademik, kepercayaan diri, kebiasaan belajar, dan motivasi belajar, serta faktor eksternal, yaitu peran guru, metode dan media pembelajaran, lingkungan belajar, dan dukungan orang tua. Penelitian ini menyimpulkan bahwa peran guru melalui penerapan metode dan media pembelajaran yang inovatif merupakan faktor yang paling dominan dalam meningkatkan minat belajar siswa. Oleh karena itu, pembelajaran Bahasa Indonesia perlu dirancang secara aktif, interaktif, dan kontekstual dengan melibatkan kolaborasi antara guru dan orang tua untuk menciptakan pengalaman belajar yang lebih bermakna.